Reversible assembly and disassembly of micelles by a polymer that switches betweenhydrophilic and hydrophobic wettings - Dutta, Kingshuk; Mahale, Rajashree Y.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Langmuir, 2012)
Supramolecular complexes involving nanoscopic amphiphilic assemblies (AAs) and polyelectrolytes have been used to prepare a variety of materials, wherein the dynamic AAs retain the structural features, but the polyelectrolytes undergo conformational changes. Here we show that a charge bearing rigid conjugated polymer can alter the structural features and disassemble AAs. We also demonstrate reversible assembly and disassembly of AAs by controlling the number of charges on the rigid polymer. During the disassembly, the guest molecules sequestered in the AAs are released. The rate of release has been modulated by changing the morphology of the charge bearing polymer. Concomitant to the AAs disassembly, the polymer surface becomes hydrophobic due to the binding of the amphiphiles on the charges of the polymer backbone. By controlling the charges on the polymer, the surface wettability was varied gradually from hydrophilic to hydrophobic.